Contrastive Analysis between English and Indonesian Word Formation - Yuspar Uzer (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractContrastive Analysis between English and Indonesian Word Formation”. The main problems of this study were as follows : (1) what are the differences between English and Indonesian word formation? (2) what are the similarities between English andIndonesian word formation? (3) What are some possible learning problems faced by Indonesian students in learning word formation in English ?. The objectives of this study were to know the differences and similarities between English and Indonesian word formation and the possible learning problem faced by Indonesian students inlearning word formation in English.In this study, the writer used descriptive method. The data were collected through documentation technique from English and Indonesian books which are relevant to the problem of the study. The data were analyzed by identifying the differences and the similarities of the word formationin the two language.The differences between English and Indonesian word formation are in the form of Affixation, confixation, Infixation, Simulfixation and Reduplication. The similarities between English and Indonesian word formation are in the form Prefixation, Suffixation, Blend, Clipping, Back-Formation and Acronym.Keywords : Contrastive Analysis, Word Formation